Calcium Dyshomeostasis Alters CCL5 Signaling in Differentiated PC12 Cells. (26th March 2019) - Radzik, Tomasz; Boczek, Tomasz; Ferenc, Bozena; Studzian, Maciej; Pulaski, Lukasz; Zylinska, Ludmila
Abstract : Background . Plasma membrane Ca 2+ -ATPase (PMCA) is the most sensitive cellular calcium detector. It exists in four main isoforms (PMCA1-4), among which PMCA2 and PMCA3 are considered as fast-acting neuron-specific forms. In the brain, PMCA function declines progressively during aging; thereby impaired calcium homeostasis may contribute to some neurodegenerative diseases. These destructive processes can be propagated by proinflammatory chemokines, including chemokine CCL5, which causes phospholipase C-mediated liberation of Ca 2+ from endoplasmic reticulum by IP3 -gated channels. Methods . To mimic the changes in aged neurons we used stable transfected differentiated PC12 cells with downregulated PMCA2 or PMCA3 and analyzed the effect of CCL5 on calcium transients with Fluo-4 reagent. Chemokine receptors were evaluated using Western blot, and IP3 receptors expression level was assessed using qRT-PCR and Western blot. Results . In PMCA-reduced cell lines, CCL5 released more Ca 2+ by IP3 -sensitive receptors, and the time required for Ca 2+ clearance was significantly longer. Also, in these lines we detected altered expression level of CCR5 and IP3 receptors. Conclusion . Although modification of PMCAs composition could provide some protection against calcium overload, reduction of PMCA2 appeared to be more detrimental to the cells than deficiency of PMCA3. Under pathological conditions, including inflammatory CCL5 action and long-lasting Ca 2+ dyshomeostasis, insufficient cell protection may result in progressive degeneration and death of neurons.